Incidencia del desarrollo del sistema bancario en el crecimiento económico en el Perú periodo 1981 - 2016 - Molina Ruiz, Marina Mercedes (2018)
The investigation analyze the incidence of the development of the Banking System in the economic growth of Peru in the period 1981-2016, during which a series of economic and social changes accompanied by a greater liberalization of the financial sector have been experienced. Therefore, it is evaluated if this development of the banking system has a positive impact on economic growth. Is analyzed performing an econometric estimation through a vector error correction model (VEC) because is a non-stationary series, integrated of the same order and presents co-integration allowing not to lose valuable long-term data and a correct specification and safety in the model. As an independent variable, takes into account the banking development, whose indicators are the transformation of savings to credit of the Multiple Banking of Peru and the Inefficiency of the Financial System of Multiple Banking; as well as, economic growth, as a dependent variable. It is demonstrated by the results that the increase in the transformation of savings to credit has a positive effect on economic growth while inefficiency behaves in a negative way due to the increase in the inefficiency of the financial system of Multiple Banking, measured by operating costs between the financial margin, decreases economic growth.